An efficient LU decomposition-based key pre-distribution scheme for ensuring security in wireless sensor networks - Pathan, Al-Sakib Khan; Dai, Tran Thanh; Hong, Choong Seon (Institute of Electrical and Electronics Engineers ( IEEE ), 2006)
In this paper we propose an improved and efficient key pre-distribution scheme for wireless sensor networks. Our scheme significantly increases the storage efficiency and security than that of the previously proposed scheme based on LU decomposition. It also ensures node-to-node mutual authentication in a way that an eavesdropper cannot harm the network by monitoring the traffic flows in the network. We also present detailed performance analysis and compare our scheme with the existing schemes.